Trademarks and The Protection for Business Actors in Indonesia: Some Contemporary Issues and Problems - Fibrianti, Nurul (Faculty of Law, Universitas Negeri Semarang, 2020)
The brand represents the identification to distinguish the results of the production of one business with other businesses, the brand is used as a product promotion tool, therefore the trademark is very important to protect the business. Through Law No. 20 of 2016, the state gives approval to all trademarks supported by businesses by requesting these trademarks. But only 4% of the number of SMEs that fulfill the trademark. Micro, small and medium business operators are not required trademarks because of their understanding and importance of trademarks, paid trademark registration and the complexity of the process and requirements for trademark registration are also additional supplements for SMEs. Therefore, there is a need for enhanced socialization of the importance of trademark registration and assistance with trademark registration.